The role of videolaryngoscope in endotracheal intubation training programs - Dagli,Recai (2018)
Abstract Background Macintosh laryngoscopes are widely used for endotracheal intubation training of medical students and paramedics whereas there are studies in the literature that supports videolaryngoscopes are superior in endotracheal intubation training. Our aim is to compare the endotracheal intubation time and success rates of videolaryngoscopes and Macintosh laryngoscopes during endotracheal intubation training and to determine the endotracheal intubation performance of the students when they have to use an endotracheal intubation device other than they have used during their education. Methods Endotracheal intubation was performed on a human manikin owing a standard respiratory tract by Macintosh laryngoscopes and C-MAC® videolaryngoscope (Karl Storz, Tuttligen, Germany). Eighty paramedic students were randomly allocated to four groups. At the first week of the study 10 endotracheal intubation trials were performed where, Group-MM and Group-MV used Macintosh laryngoscopes; Group-VV and Group-VM used videolaryngoscopes. Four weeks later all groups performed another 10 endotracheal intubation trial where Macintosh laryngoscopes was used in Group-MM and Group-VM and videolaryngoscopes used in Group-VV and Group-MV. Results Success rates increased in the last 10 endotracheal intubation attempt in groups MM, VV and MV (p = 0.011; p = 0.021, p = 0.290 respectively) whereas a decrease was observed in group-VM (p = 0.008). Conclusions The success rate of endotracheal intubation decreases in paramedic students who used VL during endotracheal intubation education and had to use Macintosh laryngoscopes later. Therefore we believe that solely videolaryngoscopes is not enough in endotracheal intubation training programs.